2022
DOI: 10.3390/app12146860
|View full text |Cite
|
Sign up to set email alerts
|

GAN-Based Image Dehazing for Intelligent Weld Shape Classification and Tracing Using Deep Learning

Abstract: Weld seam identification with industrial robots is a difficult task since it requires manual edge recognition and traditional image processing approaches, which take time. Furthermore, noises such as arc light, weld fumes, and different backgrounds have a significant impact on traditional weld seam identification. To solve these issues, deep learning-based object detection is used to distinguish distinct weld seam shapes in the presence of weld fumes, simulating real-world industrial welding settings. Genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…It has also been demonstrated that utilizing multi-scale features collected by pyramid networks can enhance the effectiveness of CNN-based dehazing [28]. GAN-based techniques [29][30][31] have been developed to address the light attenuation effect caused by haze from the original scene.…”
Section: Quadtree Decompositionmentioning
confidence: 99%
“…It has also been demonstrated that utilizing multi-scale features collected by pyramid networks can enhance the effectiveness of CNN-based dehazing [28]. GAN-based techniques [29][30][31] have been developed to address the light attenuation effect caused by haze from the original scene.…”
Section: Quadtree Decompositionmentioning
confidence: 99%